Value Chain Analysison Processing Cardava Banana Chips In The Philippines: Luzon Case - Calica, Gigi Bernardo; Lingbawan, Karen R. (International Journal of Scientific Research and Management (IJSRM), 2019)
The study aimed to provide relevant information in terms of costs and income so that more people can be enticed to go into business of banana production and processing. This was conducted in the Philippines particularly Luzon island. Value chain and descriptive analyses were used in the data processing.Research results showed that the chains for the fresh cardava to wet market and to banana chips chains involved six to eight marketing actors namely: the farmer, consolidator, trucker, wholesaler/trader or wholesaler/retailer, processor, distributor, and retailer and the consumer. All activities from the farm to the market were manually done which resulted to more or less five days to deliver the commodity from the farm to the end user.The processor received the highest gross margin share of 88.59 percent followed by wholesaler/retailer of banana chips getting around 6.25 percent share of gross margin. The farmer, agent/consolidator and wholesaler/retailer received 2.40 percent, 1.49 percent and 1.27 percent, respectively.In terms of costs, the processor incurred the highest at P4.25 per kg, the farmer at P4.16 per kg and the agent/consolidator at P2.83 per kg, both wholesaler/retailer for the fresh and processed products incurred lower costs than the other actors. Regarding income, chips wholesaler/retailer received the highest at P14.91 per kg; the processor at P6.26 per kg, and the wholesaler/retailer of fresh cardava, the farmer and the agent/consolidator received low income due to the low price of the commodity which was dependent on its quality.Fertilizer application and use of postharvest tools to improve quality of produce was recommended to receive higher price.